ANMCO POSITION PAPER: Role of intra-aortic balloon pump in patients with acute advanced heart failure and cardiogenic shock. (26th August 2021) - Rossini, Roberta; Valente, Serafina; Colivicchi, Furio; Baldi, Cesare; Caldarola, Pasquale; Chiappetta, Daniela; Cipriani, Manlio; Ferlini, Marco; Gasparetto, Nicola; Gilardi, Rossella; Giubilato, Simona; Imazio, Massimo; et al.
Abstract: The treatment of patients with advanced acute heart failure is still challenging. Intra-aortic balloon pump (IABP) has widely been used in the management of patients with cardiogenic shock. However, according to international guidelines, its routinary use in patients with cardiogenic shock is not recommended. This recommendation is derived from the results of the IABP-SHOCK II trial, which demonstrated that IABP does not reduce all-cause mortality in patients with acute myocardial infarction and cardiogenic shock. The present position paper, released by the Italian Association of Hospital Cardiologists, reviews the available data derived from clinical studies. It also provides practical recommendations for the optimal use of IABP in the treatment of cardiogenic shock and advanced acute heart failure.